IITA's Saheed celebrates International Youth Day 2022 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
Celebrating #IYD2022, IITA's Saheed shares his thoughts on Africa's youth and the role that they can play to create a world for all ages if given the opportunity.